(untitled) (Research, Society and Development, 2021)
Objective: To identify, through an integrative review of the scientific literature, studies that analyzed the effectiveness of integrative and complementary practices in the treatment of depression. Method: Qualitative integrative review that includes articles indexed in the Latin American and Caribbean Literature in Health Sciences (LILACS), Medical Literature Analysis and Retrieval System Online (MEDLINE/PubMed), Scientific Electronic Library Online (SciELO.ORG) data bases and Cochrane Library, published between 2017 and 2021, in Portuguese and English. The collection period took place in the month of October and November 2021. Results: 07 articles were included, with different methodologies, carried out in Brazil and China, the integrative practices addressed were: Auriculotherapy, Music Therapy, Mindfulness, Reike, Community Therapy and Yoga. All studies demonstrated therapeutic effectiveness in the remission of depressive symptoms and better results in the assessment of patients’ quality of life. Conclusion: The integrative practices developed for the treatment of depressive symptoms were multiple and showed statistically significant results to be used, requiring therapeutic continuity as a form of prevention and rehabilitation of the individual.